2008
DOI: 10.1103/physrevlett.100.016802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linear Density of States on the Quasiparticle Dynamics and Small Electron-Phonon Coupling in Graphite

Abstract: We obtained the spectral function of very high quality natural graphite single crystals using angle resolved photoelectron spectroscopy (ARPES). A clear separation of non-bonding and bonding bands and asymmetric lineshape are observed. The asymmetric lineshapes are well accounted for by the finite photoelectron escape depth and the band structure. The extracted width of the spectral function (inverse of the photohole life time) near the K point is, beyond the maximum phonon energy, approximately proportional t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
4
21
1
Order By: Relevance
“…Converting our values for the coupling coefficient gives λ ~ 0.06. This is considerably lower than the value for typical metals, however previous studies on weakly excited carbon have also found low coupling in room temperature graphite23 ( λ < 0.2), and graphene10 ( λ = 0.05 – 0.1). These results have been attributed to a small density of states at the Fermi energy in semimetals, an argument that becomes questionable for the high electron temperatures present in our experiment.…”
Section: Discussioncontrasting
confidence: 54%
“…Converting our values for the coupling coefficient gives λ ~ 0.06. This is considerably lower than the value for typical metals, however previous studies on weakly excited carbon have also found low coupling in room temperature graphite23 ( λ < 0.2), and graphene10 ( λ = 0.05 – 0.1). These results have been attributed to a small density of states at the Fermi energy in semimetals, an argument that becomes questionable for the high electron temperatures present in our experiment.…”
Section: Discussioncontrasting
confidence: 54%
“…For example, early data on the low-field Hall coefficient obtained in single-crystalline natural graphite (SCNG) samples showed that it is positive at fields below and negative above ∼ 0.5 T at a temperature T = 77 K, 1 suggesting that holes are the majority carriers. This result appears to be at odd to several other studies on the graphite band structure obtained in highly oriented pyrolytic graphite (HOPG) samples [2][3][4][5][6][7][8][9][10] that suggest that electrons are the majority carriers, unless one argues in terms of different mobilities of the majority carriers, an interpretation that was used indeed in the past.…”
Section: Introductionmentioning
confidence: 41%
“…5 Turns negative at large field for samples with imperfect structure. 6 system of screw dislocations or a system of edge dislocations if the misfit is in the c-direction with an angle θ c 0. A system of dislocations at the two-dimensional interfaces or topological line defects can have a large influence in the dispersion relation of the carriers 31,32 and trigger localized high-temperature superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…While the electron-phonon coupling in graphite is believed to be smaller than normal metals 49 , a large coupling constant is usually required for explaining fs laser 31,45,50 and swift ion-beam irradiation experiments 51,52 . This discrepancy reveals a complex energy exchange in nonthermally heated graphite when compared to conventional metals.…”
Section: F=64 µJ/cmmentioning
confidence: 99%